UTILIZING WORD WALL FOR VOCABULARY INSTRUCTION: A CASE STUDY IN SECONDARY SCHOOL EFL STUDENTS - Agustiani, Dini; Kusrin, Kusrin; Abas, Totoh Tauhidin (IKIP Siliwangi, 2024)
This study aims to investigate the application of words wall technique in students' vocabulary learning and to find out students' perspectives on words wall technique in vocabulary learning in EFL classroom. This research was conducted in one of the junior high schools in Indonesia. Utilizing qualitative methods, specifically a case study method with 7th grade students, data collection included observation checklist, interviews, and reflective journals. The Words Wall approach, a strategy for teaching English vocabulary, involves teachers providing key phrases or cues to stimulate student thinking. Findings indicated unanimously student positive responses to the Words Wall, highlighting its benefits in making vocabulary learning engagement and effectiveness. The technique encourages frequent practice and retention of new vocabulary, crucial for improving English comprehension as a second language. Effective implementation of Words Wall hinges on consistent selection, display, and integration into daily lessons, fostering not only academic motivation but also intellectual growth among students.